Prevalence of persistent hypertension following pregnancy complicated by hypertensive disorders in low- and middle-income countries: a systematic review - Mukosha, Moses; Hatcher, Abigail; Mutale, Wilbroad; Lubeya, Mwansa Ketty; Conklin, Jamie L.; Chi, Benjamin H. (Frontiers in Global Women's Health, 2024)
Background Hypertensive disorders of pregnancy can lead to persistent hypertension (pHTN) in the months and even years following delivery. However, its prevalence in low- and middle-income countries (LMICs) is not well characterized. Objective To synthesize available evidence on the pHTN prevalence following a pregnancy complicated by hypertensive disorders of pregnancy in LMICs. Search strategy PubMed, CINAHL Plus, Global Health (EBSCOhost), and Scopus from inception through a search date of July 12, 2022, and updated on January 2, 2024. Selection criteria Cross-sectional studies and cohort studies reporting pHTN prevalence were eligible. Data collection and analysis We conducted a narrative synthesis of data and categorized reported prevalence time points into several broader categories. We used the Newcastle-Ottawa checklist to assess the risk of bias. The protocol is registered in PROSPERO (CRD42022345739). Results We reviewed 1,584 abstracts and identified 22 studies that reported pHTN between 2000 and 2023 from 14 LMICs. The overall prevalence of pHTN ranged between 6.9% and 62.2%, with the highest prevalence noted within African studies and the lowest in South American studies. Estimates at different follow-up periods postpartum were 6.9%–42.9% at six weeks, 34.0%–62.2% at three months, 14.8%–62.2% at six months, 12.7%–61.2% at 12 months, and 7.5%–31.8% at more than 12 months. The quality score of the selected studies ranged from 50% to 100%. Conclusions The extant literature reports a high prevalence of pHTN in LMICs following a pregnancy complicated by hypertensive disorders. To reduce long-term complications of pHTN, programs should emphasize early screening and linkages to long-term care for at-risk women. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=345739, PROSPERO (CRD42022345739)